PENYULUHAN KEBIJAKAN RELAKSASI KREDIT DAN PENGAWASAN INTERNAL DI LPD TINGKATBATU, KABUPATEN BANGLI - Yudha, I Made Endra Kartika; Purwanti, Putu Ayu Pramitha; Wenagama, Wayan; Suhartika, I Putu; Haryanti, Ni Putu Premierita; Sanjaya, Putu Krisna Adwitya; Kusuma, I Wayan Gita Ayu; Sudiksa, I Wayan Dipa; Dewi, Kadek Dinda Mas Kencana (Jurnal Abdi Insani, 2024)
The Village Credit Institution (LPD) is a financial institution that is owned and managed by a traditional village in Tierbatu Village, Bangli Regency, Bali Province. LPDs have long provided support to rural communities who have difficulty accessing financial institutions such as banks due to constraints on guarantees or financial reports. Bad credit and internal monitoring are important issues, especially during a pandemic, so this is a challenge for the LPD itself because the trend for bad loans has increased. This community service aims to provide solutions to problems in the aspects of credit relaxation and internal control. The implementation method consists of counseling, mentoring, documentation and evaluation. Mentoring activities result in increased understanding of credit relaxation and internal control.